LOADING AND UNLOADING ON THE RORO FERRY DURING EXTREME WEATHER AT MERAK-BAKAUHENI PORT - Viki Ramadhani; I’ie Suwondo; Arleiny; Mustamin (Indonesian Naval Technology College STTAL, 2024)
Indonesia, an archipelagic country with 31 million km² of water and an exclusive economic zone of 27 million km², plays an essential role in the global economy. Public transportation, including land, air, and sea, dramatically affects the region's economic performance. With their roll-on-roll-off design, Roro Ferry's passenger ships are becoming an efficient and effective mode of transportation. However, they still face shortcomings in terms of safety and convenience. The research used is qualitative with a descriptive approach. The study's location is the Merak-Bakauheni Ferry Terminal, the main link between Java and Sumatra. Data was collected through interviews, observations, and case studies and analyzed using Miles and Huberman's interactive data analysis techniques. The study results show that implementing appropriate safety procedures can minimize the risk of accidents and cargo damage. Using ramp doors makes the loading and unloading easier but requires special adjustments during extreme weather. In addition, strict checks on mooring ropes, ramp doors, ventilation, and the cleanliness of the loading room, as well as the readiness of the crew, are crucial. In adverse weather conditions, additional procedures are required to handle heavy loads, such as fuso and Ironton trucks. This study provides recommendations for infrastructure improvement, revision of standard operating procedures (SOP), safety training, and collaboration with BMKG to improve safety and operational efficiency.